ANALISIS PENGARUH PAD, DAU DAN DAK TERHADAP BELANJA MODAL DAN BELANJA BARANG DAN JASA KOTA DAN KABUPATEN DI PROVINSI JAWA TIMUR TAHUN 2006-2012 - Haryanto, Sugeng (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2013)
Decentralized system of local government put as executor and promoter of development in the area to organize and define their own regional development activities in accordance with the priority needs of the local community. Local governments have the right and authority to use the vast financial resources in accordance with its needs and aspirations of the people who thrive in the area. This study aimed to analyze the effect of PAD and transfer from the central government in the form of DAU and DAK towards capital expenditure and spending on goods and services. This study took a sample of the cities and counties in the province of East Java in 2006-2012. The analysis technique used is multiple regression analysis showed that simultaneous PAD, DAU and DAK effect on capital expenditures and also to Goods and Services expenditures. Partially PAD, DAU and DAK effect on capital expenditures. While PAD and DAU partially affect Expenditure on Goods and Services, but does not affect the DAK Goods and Services expenditures.